The Role of Competency and Good School Governance in Improving Teacher Performance - Suyanto, Suyanto; Prajanti, Sucihatiningsih Dian Wisika; Kardoyo, Kardoyo; Handoyo, Eko (Universitas Negeri Semarang, 2024)
. This study investigates the role of teacher competency in mediating the influence of servant leadership, supervision systems, and school culture on teacher performance. Additionally, this study examines how good school governance influences the relationship between teacher competence and performance. The research employs a quantitative approach with a non-experimental design. It involves 289 teachers, including both civil servant and non-civil servant teachers, selected from 16 public high schools in Semarang using proportional sampling techniques. The variables examined in the study include the principal's servant leadership, school culture, supervision system, teacher competency, good school governance, and teacher performance. The research findings indicate that servant leadership has a direct influence of 25% on teacher competence, school culture has a direct influence of 30%, and the supervision system has a direct influence of 21%. Concerning teacher performance, servant leadership has a 15% influence, school culture has an 18% direct influence, and the supervision system has an 18% influence. Teacher competency also significantly affects teacher performance, with an influence of 35%. The variable of good school governance (GSG) enhances the influence of teacher competence, as indicated by an increase in the R-square value from 0.243 without moderation to 0.990 with GSG as a moderating variable.